A lipid droplet targeted fluorescent probe for high-efficiency image-guided photodynamic therapy of renal cell carcinoma. Issue 8 (7th January 2021) - Tan, Ping; Zhuang, Weihua; Li, Shufen; Zhang, Jiapeng; Xu, Hang; Yang, Lu; Liao, Yanbiao; Chen, Mao; Wei, Qiang
Abstract : A lipid droplets (LDs) specific fluorescent probe TTIE is prepared for LDs specific image-guided photodynamic therapy (PDT), which can light up the LDs in human clear cell renal cell carcinoma cells and tissues, and kill tumor cells via PDT process. Abstract : A one-step synthesized LD specific fluorescent probe TTIE with high specificity, good photostability and great capacity in generating cytotoxic reactive oxygen species (ROS) under low powered white light irradiation is designed and synthesized for LD specific image-guided photodynamic therapy (PDT) in human clear cell renal cell carcinoma (ccRCC) primary cells and tissues.